1975
DOI: 10.1007/bf02633046
|View full text |Cite
|
Sign up to set email alerts
|

Chemical analysis of polymerization products in abused fats and oils

Abstract: For more than a decade, numerous analytical methods have been proposed for the detection and measurement of polymers in vegetable fats and oils. Many of the methods have been little more than laboratory curiosities, either because they were concemed with only very specific compounds or were too cumbersome and time consuming to become very popular. More recently, a number of methods in common use for analysis of fats and oils has been shown to be useful for indirectly measuring polymeric materials in heat abuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1978
1978
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…After the oils were heated, the acylglycerol compounds were lractionated by silicic acid column chromatography (21,22). Thermal oxidation resulted in lower amounts ofacylglycerol monomeric compounds (triacylglycerols, which are relatively nonpolar reductions of ca.…”
Section: Analyses Of Oilsmentioning
confidence: 99%
“…After the oils were heated, the acylglycerol compounds were lractionated by silicic acid column chromatography (21,22). Thermal oxidation resulted in lower amounts ofacylglycerol monomeric compounds (triacylglycerols, which are relatively nonpolar reductions of ca.…”
Section: Analyses Of Oilsmentioning
confidence: 99%
“…Chemical reactions such as thermal and oxidative decompositions produce both volatile and nonvolatile products, which can have adverse effects on experimental animals (8-II). Many decomposition products, both volatile (12,13) and nonvolatile (13)(14)(15)(16)(17), have been identified during the last 20 years. However, no studies had been reported on the effects of heating with aeration on the composition of triacylglycerol species.…”
Section: Introductionmentioning
confidence: 99%
“…98% at 50 hr of the heating, 97% at 70 hr and 95% at I00 hr ( Table 2). The more polar products tended to be absorbed on the silica gel, and not eluted with the solvents (27) resulting in the lower recovery with longer heating. Therefore, the fractionated products, especially the monomers and dimers, were more purified than the original heated oils and relatively free of lipase inhibitors.…”
Section: Discussionmentioning
confidence: 99%